The Effect of Good Corporate Governance and Corporate Social Responsibility on Financial Performance - Ali Imron; Isnan Murdiansyah (Journal of Economics Education and Entrepreneurship)
This study, which focuses on data from IDX (Indonesia Stock Exchange) from 2017 to 2022, aims to explore the impact of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the financial performance of banks. The approach taken in this research is quantitative, as the analysis is based on numerical data that allows for an objective evaluation of the relationships between these variables. The findings of the study highlight the significant role of CSR in ensuring that companies, in addition to seeking profit, also consider the environmental and social impact of their operations. By adopting CSR practices, banks not only enhance their reputation but also contribute positively to the surrounding community and environment, which can ultimately lead to improved long-term financial performance. Furthermore, the study reveals a strong positive correlation between CSR and Return on Equity (ROE), indicating that banks with better CSR practices tend to experience higher financial returns. To analyze the data, the researchers apply several advanced statistical techniques, including regression analysis, which helps to explain the relationships between variables. They also conduct tests for autocorrelation, heteroscedasticity, multicollinearity, normality, and use descriptive statistics to ensure the reliability and validity of their results. These methods are crucial for confirming that the observed effects are statistically significant and not due to underlying data issues. By combining these rigorous techniques, the study provides valuable insights into how GCG and CSR practices can influence the financial outcomes of banks, with implications for both investors and policymakers who are looking to promote sustainable and ethical business practices in the banking sector.